The Water Lady : how Darlene Arviso helps a thirsty Navajo Nation - McGinty, Alice B., 1963-; Begay, Shonto (2021)
Cody is worried when his family on a New Mexico Navajo reservation runs out of water, but Darlene Arviso, called "The Water Lady," is on the way with her tanker truck. Includes glossary of Navajo terms and notes about Arviso and life on a reservation
Includes bibliographical references
Ages 4-8.
Grades K-1.
Keywords: Arviso, Darlene -- Juvenile literature; Water-supply -- Juvenile literature; Deserts -- Juvenile literature; Navajo Indians -- Juvenile literature; Indians of North America -- New Mexico -- Juvenile literature; Biography -- Juvenile literature; Sustainable living -- Juvenile literature; Navajo Indian Reservation -- Juvenile literature; Children's stories; Juvenile works; Biographies; Picture books